2016
DOI: 10.1590/0103-8478cr20150630
|View full text |Cite|
|
Sign up to set email alerts
|

Interference periods of velvet bean in sugarcane

Abstract: The objective of the present study was to determine the periods of interference of velvet bean on ratoons of sugarcane cultivar 'RB855536' and to identify its potential for decreasing 0-15, 0-30, 0-45, 0-60, 0-90, 0-120, 0-150, and 0-180 de vida: 0-15, 0-30, 0-45, 0-60, 0-90, 0-120, 0-150, 0-180

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
4
0
1
Order By: Relevance
“…Kuva et al (2001) demonstrated that losses of up to 82% were observed in areas where the predominant weed species was signalgrass, while Kuva et al (2003) verified reductions of 40% in areas with mixed infestation of signalgrass and guinea grass. Other authors have also made similar observations for other weed species in sugarcane plantations in the state of São Paulo, whose potential yield loss varied according to the type of infestation of the area (Silva et al, 2009;Piza et al, 2016;Bressanin et al, 2016).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Kuva et al (2001) demonstrated that losses of up to 82% were observed in areas where the predominant weed species was signalgrass, while Kuva et al (2003) verified reductions of 40% in areas with mixed infestation of signalgrass and guinea grass. Other authors have also made similar observations for other weed species in sugarcane plantations in the state of São Paulo, whose potential yield loss varied according to the type of infestation of the area (Silva et al, 2009;Piza et al, 2016;Bressanin et al, 2016).…”
Section: Introductionsupporting
confidence: 63%
“…Piza (2016) reported interference of I. hederifolia from 76 days after emergence, reducing crop yield by 17.5%, but this species presents a small accumulation of dry matter and macronutrients at the beginning of its cycle, being intensified at 63 days after emergence, with maximum accumulation at 139 and 140 days, for I. hederifolia and I. quamoclit, respectively, so that it can be inferred that the most intense competition can occur only at the most advanced stage of development of the crop (Carvalho et al, 2009;Guzzo et al, 2010). This contrasts with what was observed for velvet bean, which also has a climbing habit, whose interference starts at 50 days after sprouting and lasts up to 188 days, reducing yield by 50% (Bressanin et al, 2016). On the other hand, coexistence with grasses U. plantaginea, P. maximum and D. horizontalis generally provided the greatest reductions in the growth of sugarcane, mainly for variety SP80-1842.…”
mentioning
confidence: 78%
“…The loss in sugarcane yield, coexisting with densities of Brachiaria decumbens and Brachiaria brizantha equivalent to 15 plants m -2 , may reach 60% (Tironi et al, 2013) and 50% (Galon et al, 2012), respectively. On the other hand, in competition with velvet bean, the loss of yield is close to 50% (Bressanin et al, 2016).…”
Section: Resultsmentioning
confidence: 93%
“…For the soil analysis, two undisturbed soil samples were collected in each plot, at depths of 0-10 cm, at the beginning and at the end of the experiment, to assess the physical attributes of the soil. The bulk density (Ds) was evaluated by the volumetric ring method (Blake and Hartge, 1986), the particle density or real (Dp) by the volumetric balloon method and the total porosity (VTP) by calculating VTP = 100 Â (Dp À Ds)/Dp (EMBRAPA, 1997).…”
Section: Methodsmentioning
confidence: 99%